Download Darboux Transformations in Integrable Systems. Theory and by Gu C., Hu H., Zhou Z. PDF

By Gu C., Hu H., Zhou Z.

Show description

Read or Download Darboux Transformations in Integrable Systems. Theory and their Applications to Geometry PDF

Similar geometry and topology books

Low Dimensional Topology

During this quantity, that is devoted to H. Seifert, are papers in accordance with talks given on the Isle of Thorns convention on low dimensional topology held in 1982.

Additional resources for Darboux Transformations in Integrable Systems. Theory and their Applications to Geometry

Example text

After the transformation of λI − S1 , P → P = P + [J, S1 ]. Then after the transformation of λI −S2 , P → P = P +[J, S2 ], and so on. Hence, after the transformation of D, P → P + [J, S1 + · · · + Sr ] = P − [J, D1 ]. 72). (4) is proved. This proves the lemma. Darboux transformation has an important property — the theorem of permutability. This theorem originated from the B¨ a¨cklund transformation of the sine-Gordon equation and there are a lot of generalizations and various proofs. The proof here is given by [52] (2 × 2 case) and [33] (N × N case).

Since any Darboux transformation without explicit expression is a limit of Darboux transformations with explicit expressions, the theorem of permutability also holds for the Darboux transformations without explicit expressions. Now we compute the more explicit expression of the Darboux matrix of degree two. 131). Let Sj = Hj Λj Hj−1 and denote (α) (α) Λα = diag(λ1 , · · · , λN ), (α) (α) Hα = (h1 , · · · , hN ). (2) (2) (2) After the action of λI −S1 , hj is transformed to (λj I −S1 )hj . Hence H2 .

They should satisfy the following two conditions: µ where µ is a complex number (µ (1) λ1 , · · · , λN can only be µ or −¯ is not real). 241) h∗j hk = 0 holds at one point (x0 , t0 ). 241) holds at one point, then it holds everywhere. This is proved as follows. ¯ j , hence When λj = λk , λk = −λ hk,x = U (λk )hk , hk,t = V (λk )hk , ∗ ∗ ∗ ¯ j ) = −h∗ U (λk ), hj,x = hj U (λj ) = −h∗j U (−λ j ∗ ∗ ∗ ∗ ∗ ¯ hj,t = hj V (λj ) = −hj V (−λj ) = −hj V (λk ). This implies that (h∗j hk )x = 0, (h∗j hk )t = 0.

Download PDF sample

Rated 4.78 of 5 – based on 14 votes